(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
With the development of technology, the organization of pedagogical studies is increasingly taking place in a mixed way, when studies in a real classroom are combined with learning in a virtual learning environment. However, regardless of the tools or resources used in the virtual learning environment, for the organisation of student-centred studies the pedagogical aspect remains essential. This need is highlighted in the Lithuanian and European Union documents. The research aim is to analyse the learning experience of pedagogical students. Methods of research: analysis of scientific literature, survey, descriptive statistics, and inference statistics. The article reveals Primary Pedagogy and Early Childhood Pedagogy students' learning experiences in the following aspects: relevance of learning, reflective thinking, interpretation the study process, interacting with the tutor and with peers. The results of a quantitative study (survey) showed that the relevance of learning, reflection and interpretation of the study process depends on the study methods used, the support provided by the tutors and peers.